PERILAKU MAHASISWI DALAM DUNIA GEMERLAP (DUGEM) DI KOTA MANADO - Senduk, Rilya (HOLISTIK, Journal Of Social and Culture, 2016)
Modernization have made values modern enter into all society in the world. Modern values bring a lifestyle hedonic prompting the community for fashionable life and modern by the community referred to as lifestyle modern society.In Indonesia, clubbing often also called dugem, glitter world, because can be flashes of disco bright lights and thump techno music played by DJ (disk jocky) sometimes that comes from a foreign country. The clubbers derived from various levels social and age vary from teenage years until elderly are still active from immersed in world night.The clubbers is of the pledge which has had the identity of a college student who felt himself modern and would not said to be outmoded or garish because it does not follow the development of existing .Modern lifestyle is precisely a college student interested in Kota Manado to enjoy dugem activities. The involvement of girls in the sparkling caused by internal and external factors. The internal factor that is the saturated on the activities of the same, pressure obtained from activity college , the assumption that clubbers that slang, and the personal problems .The external factor is solicitation friends or acquaintance, interest that arises from social media, environmental changes promiscuity, and lack of supervision of parents or guardian. Keywords: dugem, lifestyle, clubbers.